An Approach: Molecular Imaging in Breast Cancer - Ruibal, Alvaro; Benlloch, José María; Olmos, Renato Valdés; Langstrom, Bengt (Current Topics in Medicine and Medical Research Vol. 12, 2021)
The clinical presentation of breast cancer along its evolution has changed in the last years and this fact has led to the need for new imaging techniques. A novel aspect is the molecular imaging and the use of different radiolabeling compounds in order of show and characterize it in the daily practice. In this paper we review the clinical aspects that we believe are of greatest interest.